Virenscarotins A–M, thirteen undescribed carotane sesquiterpenes from the fungus Trichoderma virens. (November 2022) - Liang, Yu; Li, Dongyan; Zheng, Yuyi; Shen, Yong; Li, Qin; Wei, Mengsha; Yang, Haojie; Ye, Saiyi; Chen, Chunmei; Zhu, Hucheng; Zhang, Yonghui
Abstract: A document investigation on the fungus Trichoderma virens led to the isolation of thirteen undescribed carotane sesquiterpenes and homologous. All structures were elucidated on the basis of NMR and HRESIMS data, and their absolute configurations were assigned by ECD calculation. Especially, virenscarotins A and B were first ramifications forged by aldol condensation of 4-hydroxy-3-isopentenyl-benzaldehyde with two hydroxyl groups in ring A of traditional carotane sesquiterpenes. Ring rearrangement/expansion and oxidative cleavage of normal carotane sesquiterpenes lead to the six-membered ring A of compound virenscarotin C and the ring A cleavage of compound virenscarotin D. All compounds were evaluated for cytotoxic, anti-inflammatory, and seed germination inhibitory activities. Graphical abstract: Thirteen undescribed carotane sesquiterpenes were isolated from the fungus of Trichoderma virens . Their structures were elucidated based on NMR, HRESIMS, and ECD calculation. Image 1 Highlights: Thriteen undescribed carotane sesquiterpenes were isolated from Trichoderma virens. Virenscarotins A and B were from condensation of benzene derivative with carotanes. Virenscarotin C was from the rearrangement/expansion of the normal carotane. Ring oxidative cleavage of normal carotane lead to compound virenscarotin D.